Racial structure of Himalayan Mahseer,Tor putitora (Hamilton) in the river Ganga between Rishikesh and Hardwar - Bhatt, J P; Nautiyal, P; Singh, H R (The Indian Journal of Animal Sciences, 2012)
Study on the racial strucutre of Tor putitora (Hamilton) was conducted in the foothill section of the river Ganga,Correlation cofficient (r)-was Â was significant at P<0.005 in all the variables except for distance between pectoral and analfin (DPA) anti pre-anal distance (PAD) during winter in relation to total length and eye diameter (ED) during monsoonin relation to head length which were significant. The F ratio was significant at P<0.05 in all the variables. The populationshowed homogenecityin the sex, season and yearsamples. The statistic r, b and F were high for standard length (SL ) inrelation to total length and post-orbital diatance (POD) in relation to head length.